Emotions Matter in Learning: The Development of a Training Package for Teachers in Higher Education - Irving-Walton, Joanne; Newton, Douglas; Newton, Lynn (International Journal for Talent Development and Creativity, 2023)
Emotions and the intellect interact and affect the quality of learning significantly, for better or for worse. This is often ignored or seen as irrelevant for teaching practices. A training package for teachers of older students was constructed to support kinds of practice which took emotions into account in planning and the classroom. In the spirit of design research intended to solve a practical problem, the package went through several iterations, each being informed by user evaluations of the preceding iteration. The outcome was a tool to support professional development. Notably and as useful, the process provided insights about diverse students’ and teachers’ attributes, variation in contexts, package adaptation to accommodate these, and areas of further research.